The ingenious gentleman and poet Federico García Lorca ascends to hell - Rojas, Carlos, 1928-2020 (Margellos world republic of letters book., 2013)
In Carlos Rojas's imaginative novel, the Spanish poet Federico García Lorca, murdered by Francoist rebels in August 1936, finds himself in an inferno that somehow resembles Breughel's Tower of Babel. He sits alone in a small theater in this private hell, viewing scenes from his own life performed over and over and over. Unexpectedly, two doppelgängers appear, one a middle-aged Lorca, the other an irascible octogenarian self, and the poet faces a nightmarish confusion of alternative identities and destinies. Carlos Rojas uses a fantastic premise--García Lorca in hell--to reexamine the poet's life and speculate on alternatives to his tragic end. Rojas creates with a surrealist's eye and a moral philosopher's mind. He conjures a profoundly original world, and in so doing earns a place among such international peers as Gabriel García Márquez, Philip Roth, J.M. Coetzee, and José Saramago.